Análisis de las muertes violentas ocurridas en Ecuador por la ingesta de bebidas alcohólicas durante 2017 – 2018. - Zapata Ortiz, Wilmer Andrés (2020)
Alcohol intake in Ecuador is a social problem that has influenced levels of violence. Using information from the statistical bases of the National Police of Ecuador regarding the crimes of femicide¸ homicide, murder and hired assassination, the relationship between alcohol consumption and violence, measured in violent deaths in the period of 2017 to 2018, in the same way the theory of the sociology of violence is taken into account, which clarifies the understanding of this problem. This article seeks to contribute to broadening our understanding of the way in which alcohol influences social actions in relation to violence. The analysis of data and information allows us to have a clear idea about the relationship between alcohol consumption and crime, such as violent deaths. Specifically, based on the analysis of the information and the statistical basis of DINASED, a comparison is made of the number of crimes for violent deaths with and without alcoholic beverages. Although the total of violent deaths produced under the influence of alcohol is not decisive, it does become a figure that contributes to the development of this theory and reflects a social problem. Finally, the study allows us to conclude that the excessive consumption of alcoholic beverages is related to the generation of violent actions in society, considering that the theory generates an important contribution to the present study.